2021
DOI: 10.1007/s10549-021-06334-0
|View full text |Cite|
|
Sign up to set email alerts
|

Full population results from the core phase of CompLEEment-1, a phase 3b study of ribociclib plus letrozole as first-line therapy for advanced breast cancer in an expanded population

Abstract: Purpose CompLEEment-1 is a phase 3b trial in an expanded patient population with hormone receptor-positive (HR +), human epidermal growth factor receptor-2–negative (HER2–) advanced breast cancer (ABC), the largest current trial of cyclin-dependent kinase 4 and 6 inhibitors in ABC. Methods Patients treated with ≤ 1 line of prior chemotherapy and no prior endocrine therapy for ABC received ribociclib 600 mg/day (3-weeks-on/1-week-off) plus letrozole 2.5 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 28 publications
8
27
0
7
Order By: Relevance
“…A total of 3,246 patients were evaluated in the overall CompLEEment-1 study over a median follow-up duration of 25.4 months and a median duration of exposure to ribociclib of 17.5 months (range, 0.0– 33 months). 26 The median TTP was 27.1 months, and the ORR was 43.6% (95% CI 41.5–45.8%). The CBR (was 69.1% (95% CI 67.1–71.1%) for patients with measurable disease at baseline.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…A total of 3,246 patients were evaluated in the overall CompLEEment-1 study over a median follow-up duration of 25.4 months and a median duration of exposure to ribociclib of 17.5 months (range, 0.0– 33 months). 26 The median TTP was 27.1 months, and the ORR was 43.6% (95% CI 41.5–45.8%). The CBR (was 69.1% (95% CI 67.1–71.1%) for patients with measurable disease at baseline.…”
Section: Resultsmentioning
confidence: 95%
“…Results from the overall CompLEEment-1 patient population demonstrated the safety, tolerability, and efficacy of ribociclib plus letrozole in this large and diverse cohort of patients with HR+/ HER2− advanced breast cancer, with a safety profile consistent with the pivotal ribociclib trials and no new safety signals. 26 The median time to progression (TTP) was 27.1 months, and the clinical benefit rate (CBR) in patients with measurable disease at baseline was 69.1% and the median PFS was 26.7 months. 26 The quality of life of patients was maintained throughout treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were more frequently available for grade 3 or more fatigue than for any-grade fatigue; rates were very low (2%) for pertuzumab + trastuzumab + paclitaxel or nab-paclitaxel (PERUSE study [82]) and trastuzumab + docetaxel (CLEOPATRA study control arm [76]), but they reached more than 20% for 100 mg/m 2 of docetaxel (15 to 24%) and gemcitabine vinorelbine (24%); in the metastatic context and according to the 5th advanced breast cancer conference guidelines, this highlights the need to favor monotherapy in such patients [101], and, when considering docetaxel, to prefer a 3w-75 mg/m 2 schedule. For BALLET: sub-analysis by ages (<70 vs. ≥70, non-comparative) 29 vs. 21 6 vs. 3 Palbociclib letrozole (PALOMA-1 and PALOMA-2) [83,95] 37-40 (ctrl: 23-28) 2-4 (ctrl: 1) Palbociclib fulvestrant (PALOMA-3) [88] 44 (ctrl: 31) 3 (ctrl: 1) Palbociclib-ET (pooled analysis PALOMA 1, 2, 3) <65 [96] 40 (ctrl: 27) 2 (ctrl: 1) 65-74 [96] 41 (ctrl: 28) 3 (ctrl: 0) ≥75 [96] 37 (ctrl: 31) 6 (ctrl: 0) Ribociclib letrozole (MONALEESA-2, CompLEEment-1) [84,97] 23-42 (ctrl: 27) 1-2 (ctrl: 1) Ribociclib fulvestrant (MONALEESA-3) [ [99] 50 (ctrl: 43) 2 (ctrl: 3) Olaparib (OlympiaAD) [100] 29 (ctrl: 23) 3 (ctrl: 1) The colors refer to the hiher reported freuency of grade 3 or more fatiue for each regime [30-40%];…”
Section: Setting Treatment Regimen and Reference Fatigue Any-grade (%...mentioning
confidence: 99%
“…Recent results from the CompLEEment-1 trial (phase 3b trial in an expanded patient population with hormone receptor-positive, human epidermal growth factor receptor-2–negative advanced BC) confirmed that safety and efficacy data in this expanded population were consistent with the data from the MONALEESA-2 and MONALEESA-7 trials and support the use of RIBO plus LET in the first-line setting for patients with HR +, HER2– advanced BC. 16 …”
Section: Safety and Quality Of Lifementioning
confidence: 99%